Does Seratonin in the intestines make you happy? - Bektaş, Atilla; Erdal, Harun; Ulusoy, Meltem; Uzbay, I. Tayfun (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Bektaş A, Erdal H, Ulusoy M, Uzbay İT. Does Seratonin in the intestines make you happy? Turk J Gastroenterol 2020; 31(10): 721-3.